The day after the dollar crashes : a survival guide for the rise of the new world order - Vickers, Damon (Hoboken, NJ : John Wiley & Sons, Inc., 2011)
'How to profit from the events leading up to the likely collapse of the U.S. dollar Society is at a crossroads. Here at home and around the world, we are living in a manner that is absolutely, unconditionally, irrevocably unsustainable. The Day After the Dollar Crashes: A Survival Guide for the Rise of the New World Order outlines the kinds of events that could trigger a global economic collapse, describing in detail the events that are likely to occur just prior to, during, and immediately following such a total collapse. It also explains how investors can profit and support a sustainable future by anticipating social trends. The book describes what government can do now to soften the dollar's fall later Details how to lead the charge to introduce innovations and solutions to meet the inevitable challenges of new kinds of economic forces Reveals how to profit by changing expectations and taking action to align investments with reality The Day After the Dollar Crashes tears away the illusions generated by politicians, media, and the financial industry to show how investors can position themselves to survive and thrive in a New World Order.'-- Provided by publisher.
Includes index.
Keywords: Dollar, American; Financial crises -- United States; Economic history -- 21st century; United States -- Economic conditions -- 2009-